Discovery of two new classes of potent monoamine oxidase-B inhibitors by tricky chemistry1. Issue 14 (18th February 2015) - Cagide, F.; Silva, T.; Reis, J.; Gaspar, A.; Borges, F.; Gomes, L. R.; Low, J. N.
<x xml:space="preserve">Abstract</x> Discovery of monoamine oxidase-B inhibitors based on chromane-2, 4-dione and chromone-3-carboxamide scaffolds for the management of neurodegenerative diseases.